Creativity and Innovation as the Foundation of Entrepreneurship in the VUCA Era: A Conceptual Perspective - Ashari, Regita Niken; Ananta, Shahrul Dwi; Winarno, Agung; Kusdiyanti, Heny (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The VUCA era characterized by volatility, uncertainty, complexity, and ambiguity requires entrepreneurial actors to possess creativity and innovation as strategic capabilities rather than merely additional attributes. This conceptual article aims to examine the role of creativity and innovation in maintaining the relevance and sustainability of entrepreneurship amid rapid and unpredictable change. Creativity enables the generation of new ideas in a flexible and adaptive manner, whereas innovation functions as a proactive strategy for responding to the dynamics of the business environment. These capabilities are influenced by organizational factors, capital, knowledge, technology, and leadership that support the creation of continuous innovation.